2009
DOI: 10.1002/jez.b.21277
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of tooth agenesis

Abstract: Tooth agenesis or hypodontia, failure to develop all normally developing teeth, is one of the most common developmental anomalies in man. Common forms, including third molar agenesis and hypodontia of one or more of the incisors and premolars, constitute the great majority of cases. They typically affect those teeth that develop latest in each tooth class and these teeth are also most commonly affected in more severe and rare types of tooth agenesis. Specific vulnerability of the last developing teeth suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
221
0
12

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(239 citation statements)
references
References 168 publications
(104 reference statements)
6
221
0
12
Order By: Relevance
“…Previous studies have mainly focused on tooth agenesis, associating the MSX1 variants to the type and number of missing teeth, and it is generally concluded that the most frequently missing teeth in case of MSX1 variants are the second premolars. [13][14][15] In a previous study we identified a novel MSX1 mutation causing tooth agenesis with cleft lip, further confirming that different MSX1 mutations may cause different phenotypes. 16 This review reveals a strong correlation between observed phenotypes and the location in the MSX1 protein structure of the disease causing mutations.…”
Section: Introductionsupporting
confidence: 57%
“…Previous studies have mainly focused on tooth agenesis, associating the MSX1 variants to the type and number of missing teeth, and it is generally concluded that the most frequently missing teeth in case of MSX1 variants are the second premolars. [13][14][15] In a previous study we identified a novel MSX1 mutation causing tooth agenesis with cleft lip, further confirming that different MSX1 mutations may cause different phenotypes. 16 This review reveals a strong correlation between observed phenotypes and the location in the MSX1 protein structure of the disease causing mutations.…”
Section: Introductionsupporting
confidence: 57%
“…13 To identify the present/absent teeth, the Fédération Dentaire Internationale tooth numbering system is used.). Both intra-and extra-oral two-dimensional (2D) photographs as well as facial 3D stereophotogrammetry images were made.…”
Section: Methodsmentioning
confidence: 99%
“…The proband was 19 years old at the time of inclusion (patient B II-3) with severe TA missing 12 permanent teeth (17,13,11,21,23,24,27,32,33,34,35,37,42,43,44,47). The upper anterior teeth show a conical aspect and the permanent upper first molars are hypoplastic.…”
Section: Family Bmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Oligodontia appears in approximately 1 in 1000 persons and may be isolated or syndromic. Genes responsible for non-syndromic oligodontia, which is generally dominantly inherited, include MSX1 (MIM 142983), PAX9 (MIM 167416), WNT10A (MIM 606268), EDA1 (MIM 300451), and LRP6.…”
Section: Introductionmentioning
confidence: 99%